Chlorin E6-photodynamic therapy basal cell carcinoma - V. N. Kapinus; M. A. Kaplan; E. V. Yaroslavtseva-Isayeva; I. S. Spichenkova; S. A. Ivanov (Исследования и практика в медицине, 2021)
Purpose of the study. Evaluation of the therapeutic efficacy of chlorin E6-photodynamic therapy (PDT) with photosensitizers (PS) photoditazine, photolone and photoran in patients suffering basal cell skin carcinoma.Materials and methods. The efficacy of chlorin E6-PDT was studied in 532 patients with basal cell skin cancer (BCC) aged 28 to 93 years. PhS Photoditazine was used in 72 (13,5 %) patients at a dose of 0.5-1.0 mg/kg, PhS Photolon - in 281 (52,8 %) patients at a dose of 1.1-1.6 mg/kg and PhS Photoran - in 179 (33,6 %) people at a dose of 1.1-1.6 mg/kg.Sessions of local irradiation of tumor foci were performed on a laser device "Latus-2" (662 nm) with a power density of 200-500 mW/cm2, light energy was applied to the tumors at a dose of 100-300-600 J/cm2.Results. During the follow-up period from 6 months to 5 years, 16.2 % of cases of relapse were diagnosed in the study group. When analyzing the results, it was found that the percentage of relapses was minimal when using all PhS in patients who underwent PDT for the first time established BCC of the initial stages (neoplasms up to 2.0 cm) and amounted to 2.2 % (4 patients out of 183), and with a prevalence of the process of more than 2.0 cm and up to 4.0 cm, 9.5 % (10 patients out of 105) of relapses were found. In the results of treatment of recurrent skin malignancies with PDT using derivatives of chloride E6, depending on the prevalence of the process, a similar trend was observed: with the size of tumor foci up to 2.0 cm, the percentage of repeated relapses was less and amounted to 17.1 % (18 patients out of 105) than in the treatment of neoplasms more than 2.0 cm and up to 4.0 cm (28.8 % of relapses - 21 patients out of 73).Conclusions. Chlorin E6-PDT makes it possible to effectively treat primary and recurrent BCC in an independent variant, and the results of treatment depend on a number of factors, including the prevalence of the disease and the presence or absence of previous treatment.